Analysis and comparative studies of code-based key encapsulation mechanisms submitted to the NIST PQC competition - Lutsenko, M.S.; Kiian, A.S.; Kuznetsova, T.Y.; Kuznetsov, A.A. (Radiotekhnika, 2018)
The error correcting code-based key encapsulation mechanisms, presented to the NIST PQC competition, are investigated. The results of the primary comparative analysis of the cryptographic properties and the performance indicators of the key encapsulation schemes are presented.